Optimizing The Use Of Information Technology In Islamic Religious Education - Nurul Hidayah; Fatkhul Helmy; Amar Jufri (Yayasan Rahmat Islamiyah, 2023)
The use of information technology in learning can certainly be done with various educational programs. As is the case in learning Islamic Religious Education, where in this case the role of media technology is also needed to get new learning and insights for students. However, this also needs to be juxtaposed with the participation of teachers or lecturers who assist students in using information technology media as an effective learning medium. Especially with the increasing ease of obtaining information and communicating which will have an impact on religious differences that can trigger differences in understanding for every world community. Thus, the role of teachers or lecturers has an important role in the use of information technology for learning activities. Where the abilities and expertise of a teacher or lecturer need to be optimized in the use of information technology as an effective learning medium for students. In this regard, the author would like to elaborate a discussion related to the optimal use of information technology in Islamic Religious Education learning activities through the approach of literature study research methods and descriptive methods. With research that discusses this matter, it is hoped that it can help and make it easier for teachers to direct students in achieving learning goals.